Nuove prospettive per l'utilizzo del remote sensing nella gestione delle emergenze da rischi Natech e l'uso della terminologia specifica - Di Franco, Sabina; Salvatori, Rosamaria; Rapisardi, Elena (GEOmedia, 2017)
The Earth Observation (EO) techniques are becoming increasingly important in risk management activities not only for natural hazards and natural disaster monitoring but also to ride out industrial and Natech accidents. The latest development in the aerospace industry such as sensors miniaturization and high spatial and temporal resolution missions devoted to monitoring areas of specific interest, have made the use of EO techniques more efficient and ready to use in near real time conditions. This paper summarize the current state of knowledge on how EO data can be useful in manage all the phases of the Natech disaster, from the environmental conditions before the accident strikes to the post accident relief, from the scenario setting and planning stage to damage assessment. Moreover some terminological tools are proposed NHWikisaurus and EOSterm thesaurus, that could be useful for semantic knowledge spreading in EO and risk managment.